1999
DOI: 10.1046/j.1365-294x.1999.00726.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of landscape on the population genetic structure of the alpine butterfly Parnassius smintheus (Papilionidae)

Abstract: Four microsatellite DNA markers were developed which were used to examine the relationship between landscape and population genetic structure among a set of populations of the butterfly Parnassius smintheus located in the foothills of the Canadian Rockies. Detailed information on the dispersal of adult butterflies among this same set of populations was available. Simple and partial Mantel tests were used to examine the relationships between genetic distances, predicted rates of dispersal, and a number of lands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
232
1
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 195 publications
(246 citation statements)
references
References 57 publications
10
232
1
3
Order By: Relevance
“…In particular, in other Parnassius sp. populations studied with microsatellite loci (MeglŽcz et al 1998;Keyghobadi et al 1999Keyghobadi et al , 2002Petenian et al 2005), the observed heterozygosity ranges between 0.33Ð0.68, a range into which our results fit well.…”
Section: Differences In Genetic Diversitysupporting
confidence: 75%
“…In particular, in other Parnassius sp. populations studied with microsatellite loci (MeglŽcz et al 1998;Keyghobadi et al 1999Keyghobadi et al , 2002Petenian et al 2005), the observed heterozygosity ranges between 0.33Ð0.68, a range into which our results fit well.…”
Section: Differences In Genetic Diversitysupporting
confidence: 75%
“…DNA was extracted from wingclips using a DNeasy Blood and Tissue Kit (QIAgen), with a final elution volume of 200 μL. Each sample was genotyped at seven highly variable microsatellite loci (28,29). PCR amplification of microsatellites occurred in two multiplex amplifications (multiplex 1: Ps 50, Ps 81, and Ps 85; multiplex 2: Ps 76 and Ps 163) and two individual locus amplifications (Ps 262 and Ps 165).…”
Section: Methodsmentioning
confidence: 99%
“…using . Homozygote excess at these loci is known to be a result of null alleles (28,29), which are nonamplifying alleles that result from variation in microsatellite flanking regions. Null allele frequencies were estimated, and frequencies of other alleles were simultaneously reestimated, using the ENA method in the software FreeNA (32).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is primarily caused by the frequent occurrence of null alleles (Cassel, 2002;Jiggins et al, 2005;Van't Hof et al, 2005). There is substantial evidence that many null alleles in Lepidoptera are caused either by mutations in primer binding sites resulting in unsuccessful PCR, or by indels that produce alleles with PCR fragment sizes which fall outside the standard detection range (Palo et al, 1995;Keyghobadi et al, 1999;Reddy et al, 1999;Flanagan et al, 2002;Jiggins et al, 2005). Therefore, this relatively high flanking sequence variability, that manifests itself as null alleles, is in part responsible for the low yields.…”
Section: Introductionmentioning
confidence: 99%